Testing the Effect of Flight and Scan Strip Alignment Parameters on the Accuracy of the Point Cloud Obtained by the DJI Zenmuse L1 Lidar System - Boušek, Martin (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This paper deals with testing the effect of flight and scan strip alignment parameters on the accuracy of the point cloud obtained by the UAV-mounted DJI Zenmuse L1 lidar system. The flight parameters tested are the scanning mode, the cross-strip overlap size, and the flight speed. The strips were aligned in the TerraMatch software by using the vector tying features and the ICP algorithm. The accuracy of the aligned point clouds was determined by comparison with a triangular terrain model obtained by photogrammetry.
Keywords: Lidar; UAV; point cloud; TerraMatch